Growth Responses of Acacia mangium and Paraserianthes falcataria Seedlings on Different Soil Origin under Nursery Condition - Tirtha Ayu Paramitha; Djumali Mardji (Graduate Program of Syiah Kuala University, 2015)
The objective of the present study was to examine the growth responses of Acacia mangium (mangium) and Paraserianthes falcataria (sengon) seedlings growing on different soil origin under nursery condition. This study was started in September 2012 and terminated in March 2013. The seedlings were grown from seeds sown in a plastic box filled with sterilized sands. One week after sowing, the seedlings were transplanted into polybags contained sterilized soils originated from secondary forest, Imperata cylindrica grassland and ex-coal mining. The number of all seedlings were 180 seedlings consisted of 3 different soils, 2 species of seedlings with 10 seedlings replicated 3 times. Assessment was conducted one week after transplanting, then subsequently monitored every 2 weeks, except dry weighing and counting nodules were performed at the end of the study. A completely randomized design was used in this study. The data was analyzed using Costat software. The study resulted that the different of soil origin influenced on all growth variables of mangium and sengon of 4.5 months old. The survival rate of seedlings, height and diameter increments, dry weight and root nodules were better in both species of seedlings growing on soil originated from secondary forest and Imperata grassland compared with the soil from ex-coal mining. But the survival rates of sengon seedlings were higher than that of mangium on these three soils. The highest dry weight of sengon seedlings was achieved on soil originated from secondary forest. In the present study, soil originated from secondary forest increased more in weight of shoot than root, so that the shoot-root ratio was unbalanced more than one. Based on the results of this study, it is recommended that soil from secondary forest and Imperata grassland can be used as growing media for mangium and sengon seedlings in the nursery.